Cyberpunk 2077. Volume 3, blackout - Sztybor, Bartosz (Dark Horse Books, 2023)
"In a hi-tech future, a virtual reality technician struggles with enabling the harmful effects of the company he works for as rolling blackouts threaten the city-and virtual reality users"--